Board Evaluations : Insights from India and Beyond - Larson, Mary Jo; Pierce, Chris (International Finance Corporation, Washington, DC, 2015)
Board evaluation has emerged as a corporate governance priority and brought to the forefront many associated challenges. This is not a revolutionary change. Board assessment procedures are evolving as nations and companies formulate and test diverse requirements. Until recently effective Board evaluation was not regarded a Board priority. In 2002, Yale University Professor Jeffrey Sonnenfeld commented: ‘I can’t think of a single work group whose performance gets assessed less rigorously than corporate Boards.’ India has moved to the forefront of this governance challenge with its new Companies Act of 2013, which states that the Board of every listed company and other public companies with paid-up capital of Rs 25 crore or more (approximately US$ 4 million) shall report the annual performance evaluation of individual directors, the Board and its committees. However, in the last 12 years the situation has substantially changed. Corporate governance practitioners have been applying Peter Drucker’s idea that ‘what gets measured gets managed,’ and among senior leaders, what gets acknowledged and valued gets done even better. Recognizing the merits of various approaches, we highlight the Board’s leadership culture, the tone at the top, as an essential feature of an effective assessment process. Board evaluation is driven by the values and performance expectations of senior leaders in Tata Group, Infosys and other well-known Indian companies. Topics addressed in this article include: incentives for Board evaluation; extent of Board evaluation globally; significant requirements in India; predictable barriers and challenges; case example of Board leadership from India; recommended practices worldwide; and future trends and challenges.